Dynamic Resource Management in IoT-Enabled Health Monitoring Systems - Anzanpour, Arman (fi=Turun yliopisto|en=University of Turku|, 2025)
ABSTRACT In recent years, health technologies have become game-changers in addressing healthcare accessibility issues. Despite advancements, quality medical care was not available to everyone for many years due to geographical constraints, limited resources, and high costs. Utilizing remote health services, health technologies are reshaping this situation, offering solutions for universal healthcare access. This thesis delves into the impact of health technologies, with a focus on IoT-enabled remote health monitoring systems and their potential to revolutionize healthcare delivery. Real-time health assessments and early interventions can be signifcantly improved by miniaturizing hospital-grade monitoring devices into IoT-based wearables capable of collecting and transmitting biosignals. However, the deployment of IoT-based health monitoring systems faces challenges, mainly related to system resources. The thesis underscores the importance of effective resource management in optimizing these systems where static resource management involves selecting hardware components during design, and dynamic management at runtime ensures adaptability and real-time responsiveness. Self-awareness enables systems to autonomously monitor, analyze, and adapt their components and behaviors in real-time. Context-awareness allows the system to recognize and respond to environmental and operational contexts, balancing data quality and resource effciency. Goal management aligns and prioritizes multiple objectives, such as emergency responses, measurement accuracy, and battery optimization, to dynamically allocate resources based on real-time needs. Computation offoading entails redistributing computational tasks across different system layers to maintain performance and timely responses, especially under constrained network conditions. These methodologies aim to extend hospital-grade early warning systems to home environments, thereby improving the management of chronic conditions and patient outcomes. The strategic resource management approaches ensure that IoT-based health monitoring systems are robust, effcient, and capable of providing continuous, high-quality patient care. KEYWORDS: Health Technology, Internet of Things (IoT), Remote Health Monitoring, Early Warning Score Systems, Resource Management

TIIVISTELMÄ Terveysteknologian kehitys viime vuosina on parantanut terveydenhuollon saavutettavuutta. Tästä positiivisesta kehityksestä huolimatta laadukas terveydenhuolto ei ole maantieteellisten rajoitusten, rajallisten resurssien ja korkeiden kustannusten vuoksi kaikkien saatavilla samalla tavalla. Etäpalveluita hyödyntämällä terveysteknologia on muuttamassa tilannetta ja tarjoaa ratkaisuja terveydenhuollon yleiseen saavutettavuuteen. Tässä väitöskirjatyössä tarkastellaan digitaalisten ratkaisujen vaikutusta etäterveydenseurantaan, keskittyen erityisesti esineiden internetin avulla toteutettuihin etäterveydenseurannan järjestelmiin ja niiden mahdollisuuksiin parantaa terveydenhuollon saavutettavuutta. Erilaisia terveydenseurannan laitteita voidaan pienentää puettaviksi esineiden internet pohjaisiksi laitteiksi, jotka pystyvät keräämään ja lähettämään käyttäjän biosignaaleja kuten esimerkiksi tietoja sydämen toiminnasta ja happisaturaatiosta. Näiden laitteiden käyttöönotossa on kuitenkin haasteita, jotka liittyvät pääaasiassa järjestelmäresursseihin. Väitöskirjassa korostetaan tehokkaan resurssienhallinnan merkitystä näiden järjestelmien optimoinnissa, jossa staattinen resurssienhallinta käsittää laitteistokomponenttien valinnan järjestelmän suunnittelun aikana ja dynaaminen hallinta käytönaikaisen mukauttamisen ja reaaliaikaisen reagointikyvyn optimoinnin muuttuvassa käyttöympäristössä. Vaitöskirjatyössä toteutettu itsetietoisuus mahdollistaa järjestelmän komponenttien ja toiminnan autonomisen valvonnan, analysoinnin ja mukauttamisen reaaliajassa. Kontekstin tunnistaminen, kontekstitietoisuus, mahdollistaa järjestelmän toimintaympäristön ymmärtämisen ja siihen reagoimisen, minkä avulla voidaan tasapainottaa biosignaalien laatua ja resurssitehokkuutta. Tavoitehallinta auttaa asettamaan ja priorisoimaan useita tavoitteita samanaikaisesti – kuten hätätilanteisiin reagointi, mittausten tarkkuus ja akun virrankulutuksen optimointi – ja ohjaamaan resurssien dynaamista allokointia reaaliaikaisen tarpeen mukaan. Järjestelmä hyödyntää myös laskentatehon dynaamista siirtämistä jonka avulla voidaan jakaa laskennallisten tehtävien eri järjestelmätasojen välillä suorituskyvyn ja oikeaikaisen ajoituksen varmistamiseksi. ASIASANAT: Terveysteknologia, esineiden internet, terveyden etäseuranta, varhaisvaroitusjärjestelmät, resurssienhallinta